Diagnostics and treatment of diverticular disease of the colon: guidelines of the Russian gastroenterological Association and Russian Association of Coloproctology - V. T. Ivashkin; Yu. A. Shelygin; S. I. Achkasov; S. V. Vasilyev; Ye. G. Grigoryev; V. V. Dudka; B. N. Zhukov; O. Yu. Karpukhin; A. M. Kuzminov; V. F. Kulikovsky; T. L. Lapina; A. V. Lakhin; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.